Detection of Helicobacter pylori carriers by discriminant analysis of urea and pH levels in gastric juices. Issue 8 (August 1991) - Ameglio, F; Abbolito, M R; Giannarelli, D; Citarda, F; Grassi, A; Gandolfo, G M; Casale, V
Abstract : An alternative approach to the problems inherent in current methods for detecting Helicobacter pylori carriers–that of being generally time-consuming, expensive, and not sufficiently sensitive–was devised by using the urea concentration and pH levels of gastric juices. A linear discriminant analysis of these variables, measured in 54 patients submitted to digestive endoscopy for gastritis, provided a mathematical formula for assigning the subjects (previously classified by other standard methods) to groups of either positive or negative H pylori carriers. The results obtained showed a correct classification in 52 out of 54 cases with only one false negative and one false positive case.